Experimental Observation of the Temperature at the Liquid/Gas Interface; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Velicanov V. D.; Orlova E. G. Evgeniya Georgievna; Saigash A. S. Anastasiya Sergeevna; Korneva O. S. Olga Sergeevna (2016, 2016)
Title screen